Why Does Synergistic Activation of WASP, but Not N-WASP, by Cdc42 and PIP2 Require Cdc42 Prenylation?. Issue 8 (15th April 2023) - Dey, Souvik; Zhou, Huan-Xiang
Graphical abstract: Highlights: WASP is autoinhibited until activated by binding PIP2 to BR and Cdc42 to GBD. PIP2 binding is diminished by binding to Cdc42 and restored upon Cdc42 prenylation. Cdc42 prenylated is required for activation of WASP but not of close homolog N-WASP. The difference is traced to the number of basic residues in BR and spacing from GBD. Abstract: Human WASP and N-WASP are homologous proteins that require the binding of multiple regulators, including the acidic lipid PIP2 and the small GTPase Cdc42, to relieve autoinhibition before they can stimulate the initiation of actin polymerization. Autoinhibition involves intramolecular binding of the C-terminal acidic and central motifs to an upstream basic region and GTPase binding domain. Little is known about how a single intrinsically disordered protein, WASP or N-WASP, binds multiple regulators to achieve full activation. Here we used molecular dynamics simulations to characterize the binding of WASP and N-WASP with PIP2 and Cdc42. In the absence of Cdc42, both WASP and N-WASP strongly associate with PIP2 -containing membranes, through their basic region and also possibly through a tail portion of the N-terminal WH1 domain. The basic region also participates in Cdc42 binding, especially for WASP; consequently Cdc42 binding significantly compromises the ability of the basic region in WASP, but not N-WASP, to bind PIP2 . PIP2 binding to the WASP basic region is restored only when Cdc42 is prenylated at the C-terminus and tethered to the membrane. This distinction in the activation of WASP and N-WASP may contribute to their different functional roles.